2011
DOI: 10.1021/jo201184p
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Organocatalytic Friedel–Crafts Alkylation Reaction of Indoles with 5-Hydroxyfuran-2(5H)-one: Access to Chiral γ-Lactones and γ-Lactams via a Ugi 4-Center 3-Component Reaction

Abstract: 5-Hydroxyfuran-2(5H)-one 1, a readily available renewable resource, was used as an electrophile in the Friedel-Crafts alkylation of indoles catalyzed by a diphenylprolinol silyl ether. Moderate catalyst loading was achieved because of the high reactivity of 5-hydroxyfuran-2(5H)-one 1 in this process. Reduction of the Friedel-Crafts adduct (FC adduct) afforded indoyl lactones in high yield and enantioselectivity. Moreover, the FC adduct was used as a chiral synthon in a diversity-oriented synthesis, as illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…We have previously established that iminium activation of 1 is efficient in both anhydrous conditions and in the presence of a large excess of water, as exemplified in Friedel−Craft reactions. 16 In the present reaction conditions, the boric acid, which accumulates during the reaction course, can unfavorably interfere with the catalytic cycle. We think that the addition of an optimized amount of water might limit this interference.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We have previously established that iminium activation of 1 is efficient in both anhydrous conditions and in the presence of a large excess of water, as exemplified in Friedel−Craft reactions. 16 In the present reaction conditions, the boric acid, which accumulates during the reaction course, can unfavorably interfere with the catalytic cycle. We think that the addition of an optimized amount of water might limit this interference.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…15 We demonstrated that 5-hydroxyfuran-2(5H)-one 1, a readily available biobased molecule, can be engaged in an efficient one pot sequential process involving an enantioselective organocatalytic Friedel−Crafts and a 4-center 3-component Ugi reaction. 16 In order to further demonstrate the usefulness of 1 as reactant in both organocatalytic and multicomponent reaction processes, we described herein a one pot sequential procedure involving the organocatalytic enantioselective transfer of a boronic acid substituent and the subsequent transformation of the intermediate into an α,γ-substituted chiral lactone via an intramolecular Passerini type reaction (Scheme 1). 17 Inspired by the mechanism of the Petasis reaction, 18−20 efficient enantioselective organocatalytic transfers of boronic acids to α,β-unsaturated carbonyl compounds have been recently reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2012, Hasimoto 38 and his group reported a new asymmetric Ugi reaction involving N′ alkylbenzohydrazide 98, benzaldehydes and various isocyanides using axially chiral dicarboxylic acid (R)-97 as catalyst (Scheme 48). This reaction proceeded through an azomethine imine intermediate.…”
Section: Scheme 47mentioning
confidence: 99%
“…Indole derivatives with a strong electron‐withdrawing substituent were applied. The 4‐cyano‐functionalized indole 14 g has been gradually transformed to the desired lactone in a good yield and moderate enantioselectivity (91 : 9) (Scheme , Table ) …”
Section: Organocatalyzed Asymmetric Friedel‐crafts Reactions Usingmentioning
confidence: 99%
“…The 4cyano-functionalized indole 14 g has been gradually transformed to the desired lactone in a good yield and moderate enantioselectivity (91 : 9) (Scheme 92, Table 40). [120] A unique enantioselective organocatalytic 1,6-addition/ 1,4-addition sequence to 2,4-dienals was achieved. based on a 1,6-F-C/1,4-oxa-Michael cascade, the organocatalyst directs the reaction of hydroxyarenes with a vinylogous iminium-ion intermediate to afford only one out of four possible 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 regioisomers, thus affording optically active chromans in excellent yields and 94-99 % enantioselectivity.…”
Section: Diarylprolinol Ethersmentioning
confidence: 99%